Jaskra u pacjenta z krótkowzrocznością – problemy diagnostyczne - Urban, Beata (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Myopic eyes represent a special problem in the diagnosis of glaucoma. First, glaucomatous changes of the optic disc can be masked by the usual myopic conus, tilting of the disc and circumpapillary atrophy. Second, the ocular rigidity is usually lower than in normal eyes, therefore intraocular pressure must be checked with applanation or contour tonometry. Third, glaucomatous changes in the visual field of myopic patient may be thought to be caused by the myopic conus, staphyloma or choroidal atrophy. The discerning clinician must be doubly on guard for glaucoma in myopic patients. This is especially important because glaucoma occurs more frequently in myopic patients.